The Effect of Customer Satisfaction, Service Quality, Customer Experience, and Trust on Customer Loyalty at Point Coffee Rajawali Branch in Palembang City - Agung Wijaya; Nyimas Artina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
A This study aims to examine the influence of customer satisfaction, service quality, customer experience, and trust on customer loyalty at Point Coffee Rajawali Branch in Palembang. This research used a quantitative approach with a causal associative design. The population consisted of 310 customers, and 175 respondents were selected using purposive sampling based on the Slovin formula with a 5% error tolerance. Data analysis was conducted using multiple linear regression.The results show that customer satisfaction, service quality, and customer experience have a positive and significant effect on customer loyalty. Meanwhile, trust does not have a significant effect on customer loyalty. Simultaneously, all independent variables significantly influence customer loyalty. Customer satisfaction is the most dominant factor affecting customer loyalty at Point Coffee Rajawali Palembang.